Conservation Priorities and Demographic History of Saussurea involucrata in the Tianshan Mountains and Altai Mountains - Lin Hu; Ting Lu; Xiyong Wang; Jiancheng Wang; Wei Shi (Life, 2023)
Rare and vulnerable endemic plants represent different evolutionary units that occur at different times, and protecting these species is a key issue in biological protection. Understanding the impact of the history of endangered plant populations on their genetic diversity helps to reveal evolutionary history and is crucial for guiding conservation efforts. Saussurea involucrata, a perennial alpine species mainly distributed in the Tianshan Mountains, is famous for its medicinal value but has become endangered due to over-exploitation. In the present study, we employed both nuclear and chloroplast DNA sequences to investigate the genetic distribution pattern and evolutionary history of S. involucrata. A total of 270 individuals covering nine S. involucrata populations were sampled for the amplification and sequencing of nrDNA Internal Transcribed Spacer (ITS) and chloroplast trnL-trnF, matK and ndhF-rpl32 sequences. Via calculation, we identified 7 nuclear and 12 plastid haplotypes. Among the nine populations, GL and BA were characterized by high haplotype diversity, whereas BG revealed the lowest haplotype diversity. Molecular dating estimations suggest that divergence among S. involucrata populations occurred around 0.75 Ma, coinciding with the uplift of Tianshan Mountains. Our results reveal that both isolation-by-distance (IBD) and isolation-by-resistance (IBR) have promoted genetic differentiation among populations of S. involucrata. The results from the ecological niche modeling analyses show a more suitable habitat for S. involucrata in the past than at present, indicating a historical distribution contraction of the species. This study provides new insight into understanding the genetic differentiation of S. involucrata, as well as the theoretical basis for conserving this species.